Impact of High Commitment HRM Practices on the Non-Academic Staff Performance: Mediating Role of Affective Commitment and Job Satisfaction - Muhammad Ahtisham ul haq; Kashif Mehmood; Zia-ur-Rehman Rao; Asad Abbas (Journal of Business and Social Review in Emerging Economies, 2022)
Purpose: The purpose of this study is to scrutinize the relationship between non-academic staff and student support services by developing a conceptual model of the mediation impact of affective commitment and job satisfaction on the relationship between high commitment HRM practices and non-academic staff performance.